Protocolo de Procedimientos para la Construcción de Obras Civiles en la Cooperativa de Productores de Leche Dos Pinos R.L - Ulloa-Ávila, Ricardo José (Instituto Tecnológico de Costa Rica, 2007)
The Developer project corresponds to a construction procedure of the civil works for Dos Pinos. The object of the project is to elaborate a procedure that allows identifying the different stages of the construction process, and guarantee the quality of each of the projects stages. The following stages have been identified in order to guarantee the quality of the construction process: budget, construction permits, biding, initial works, inspection process during the construction stages, closing works and historic, these are the fundamentals aspects that need to be taken into consideration. In this project on site work was a key element in order to recompiles the necessary data in order to elaborate a written document. Blank forms and substantial documentations were used to back up the investigation work. The result was the elaboration of a basic protocol of procedures for the company. This protocol will allow Dos Pinos to be more organized in their constructions process making their projects substantially simpler to manage.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica; Escuela de Ingeniería en Construcción, 2007.
Keywords: Presupuesto; Aseguramiento de la calidad; Licitación; Procesos de inspección; Proceso de ejecución